Selfing rate estimation in sugarcane under unfavorable natural conditions of crossing by using microsatellite markers - Melloni, M. L. G. [UNESP]; Scarpari, M. S.; Pinto, L. R.; Perecin, D. [UNESP]; Xavier, M. A.; Landell, M. G. A. (Funpec-editora, 2014)
The self-fertilization or selfing rate estimation using microsatellite markers and its impact on survival and selection rate were evaluated in families derived from polycrosses that involved parents that were widely used in sugarcane breeding in Brazil. These factors were evaluated under unfavorable natural conditions of flowering and crossing. After the germination test, the viable progeny were taken to the field for survival rate evaluation (4, 6, and 10 months) and phenotypic selection at plant cane. The selfing rate estimate based on microsatellite markers present in the progeny and absent in their female parent was 98.5 and 0% for the polycross families derived from IACSP95-5000 and SP89-1115, respectively. The survival and selection rates in the last 2 evaluations were higher for the SP89-1115 outcrossed family than the IACSP95-5000 selfed family. The IACSP95-5000 cultivar excelled either as pollen donor with fertilization capability or viable seed production even under unfavorable natural conditions of crossing. The environment influence (temperature and humidity) had an important role during the polycross.
Keywords: Saccharum spp.; flowering; Pollen viability; Molecular markers